Collaborative Advantage in Public and Social Services: the Case of Poland - Maria Janina Szymankiewicz (Entrepreneurial Business and Economics Review)
This article seeks to analyse the relationships between the third and the public sector, with a particular focus on relations with local government units (LGUs) on the example of Poland. The article characterises the essence and rules of collaboration between the social and public sectors in Poland, and determines the meaning of the cooperative development of strategy of collaborative advantage. It also presents a useful tool which facilitates the realisation of such a task – a model of strategic cross-sector collaboration.